The relationship between maternal health literacy with physical activity self-efficacy in postpartum women - Masoumeh Masoumy; Soudabeh Hamedi-Shahraki; Fatemeh Zeraatpishe (Shahrekord University of Medical Sciences, 2024)
Background and aims: For women of reproductive age, postpartum weight retention can increase the risk of obesity and its associated health risks in women. Adequate health literacy can improve women's self-efficacy regarding their ability to adhere to physical activity postpartum. The study aimed to determine the relationship between health literacy and physical self-efficacy in postpartum women referred to comprehensive health service centers in Bushehr city. Methods: This cross-sectional study (descriptive-analytical) was performed on 130 women with children under three months, referring to comprehensive health service centers in Bushehr city. Subjects were selected using a multi-stage cluster random sampling method of 10 comprehensive health service centers in Bushehr city. The required data were collected using the Maternal Health Literacy and Pregnancy Outcome Questionnaire (MHLAPQ) and the Physical Self-efficacy Questionnaire. Descriptive statistics, ANOVA, independent t-test, and Pearson correlation were applied to analyze the data using SPSS 20. The level of statistical significance was P value<0.05. Results: The mean score for maternal health literacy was 51.17±5.53, so the lowest score was 14, and the highest was 56. A positive and significant correlation existed between maternal health literacy and physical activity self-efficacy (r=0.196, P<0.05). Significant relationships were found between maternal health literacy and physical self-efficacy postpartum with educational level and job mothers (P<0.05). Conclusion: Considering the relationship between health literacy and increasing physical activity self-efficacy and improving postpartum weight management, training workshops for promoting health literacy and consequently self-efficacy and physical activity in health centers should be developed.